The Effect of Product Quality, Price Perception and Promotion on Customer Satisfaction and its Impact on Customer Loyalty of PT Makmur Jaya Agro Pesticides - Mifta Elfahmi; Suharyono (Open Access Indonesia Journal of Social Sciences, 2021)
This study aims to determine the direct effect of Product Quality, Price Perception and Promotion on Consumer Satisfaction of PT Makmur Jaya Agro's pesticides, as well as to determine the indirect effect of these variables on Customer Loyalty through Customer Satisfaction. As many as 160 respondents of PT Makmur Jaya Agro's pesticide consumers who came from the Subang Regency area were the objects of this study. The research model used the Structural Equation Model (SEM) with the help of analysis tools SPSS Version 26 and Lisrel Version 8.30. The results showed that Product Quality, Price Perception and Promotion had a positive and significant effect on Customer Satisfaction. Customer Satisfaction is an intervening variable dependent on customer loyalty where Product Quality, Price Perception and Promotion have a positive and significant effect on Customer Loyalty through Customer Satisfaction. This research can be useful for companies to identify, plan and manage steps and policies to increase Customer Satisfaction and Customer Loyalty.